(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, four samples of Bi2-ycdySr2Ca.2Cu3O10+δ with y= 0.1, 0.2, 0.3 and 0.4 have been prepared by solid state reaction process. The powder was pressed to pellets with one cm diameter under a hydrostatic pressure about (8 tons/cm2). The pellets were put in a furnace which has a programmable controller for sintering in air at 855–860 ◦C for 72 hours with a rate of `100 °C /hours and then were cooled to room temperature by same rate of heating. Electric resistivity was studied using the four probe technique to find the transition temperature at zero resistivity (Tc(off)) and on set (Tc(on)), The transition temperature Tc(off) and Tc(on) were increasing from 106 to 131 K and 113 to 138 K by increasing cadmium from 0 to 0.4, respectively. X-ray diffraction (XRD) analysis showed all our samples have orthorhombic structure correspond to the 2223 phase, with changing of the intensity by increasing cadmium concentration.